2005
DOI: 10.1002/ijc.21244
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle habits as prognostic factors in survival of laryngeal and hypopharyngeal cancer: A multicentric European study

Abstract: Little information is available on the role of tobacco, alcohol and diet in the survival of upper aero digestive cancers. Our study analysed the survival of 931 laryngeal and hypopharyngeal cancer patients, enrolled in a population based case-control study conducted at 5 centres in southeast Europe during 1979Europe during -1982. Age at the time of diagnosis and site of origin of tumour were observed to be predictors of the survival. Cigarette smoking, and to a limited extent alcohol drinking, before the diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
67
2
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 9 publications
4
67
2
5
Order By: Relevance
“…2,21 Demographic factors such as age, sex, race, familial history of cancer, socioeconomic status, lifestyles, and habits (tobacco, alcohol, and substance abuse) are only a few of the many factors that impact outcomes of treatment. 13,14,22,23 Clinicians regularly use this information in the decision-making process for treatment of patients with cancer. However, none of the other host characteristics have representation in the current staging system for oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…2,21 Demographic factors such as age, sex, race, familial history of cancer, socioeconomic status, lifestyles, and habits (tobacco, alcohol, and substance abuse) are only a few of the many factors that impact outcomes of treatment. 13,14,22,23 Clinicians regularly use this information in the decision-making process for treatment of patients with cancer. However, none of the other host characteristics have representation in the current staging system for oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Results concerning patient survival and the occurrence of SPTs according to demographic and lifestyle factors recently have been published. 3,13 Surgical paraffin-embedded tissue (PET) sections were collected for the current study from 235 patients who had complete follow-up information available. The patients were comprised of 155 men and 12 women from the city of Turin, Italy, and 67 men and 1 woman from the province of Navarra, Spain.…”
Section: Study Populationmentioning
confidence: 99%
“…1 Previously, we described the role of clinical and lifestyle-related factors in the prognosis for patients with laryngeal and hypopharyngeal cancer. 2,3 Recent studies also have investigated the role played by genetic and epigenetic alterations in the progression to head and neck cancer 4,5 and, specifically, have analyzed the cytosine methylation of CpG islands in gene promoters. It has been suggested that aberrant promoter methylation is associated with loss of gene function that can provide a selective advantage for neoplastic cells, similar to what occurs in mutations.…”
mentioning
confidence: 99%
“…Some studies report an inverse association between alcohol intake and survival,13, 19, 20, 21 whilst others have found little or no evidence of an effect 17, 22. Consequently, it is unclear whether any association of alcohol consumption with HNC cancer mortality is genuine, or the result of residual confounding by smoking (or other factors).…”
mentioning
confidence: 99%